Preferensi Hunian Sementara bagi Penerima Manfaat Program Pengembangan Perumahan di Kawasan Kumuh Kelurahan Bira Makassar - Andi Annisa Amalia; Ahmad Sarwadi; Muhammad Sani Roychansyah (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2024)
Temporary housing for beneficiaries of the Housing Development Program in the slum area of Kelurahan Bira Makassar is interesting to study because its fulfillment is pursued independently by target households. This research aims to understand their preferences for temporary housing during the development process. This research uses the grounded theory method with a content analysis approach and open coding technique. The results show that preferences for temporary housing include: (1) space needs such as bedrooms, toilets, and kitchens; (2) locations close to places of worship, health facilities, village offices, and permanent housing construction locations; and (3) free from rental fees. Beneficiary priority preferences include basic domestic needs that are short-term in nature. Understanding these preferences is important in designing settlements that are more suited to local needs based on the wishes and needs of residents.